Dinamika islam dan Politik Elit - Elit Muhammadiyah Periode 1998-2010 - RIDHO AL HAMDI (Jurnal Studi Pemerintahan, 2012)
This research studied on political elite in Muhammadiyah as moderate representatives in post-NewOrder in response of the dynamics Islam and politics. There are three issues as basic analyzes, i.e. theemergence of Islamic political parties, the desire of returning the Jakarta Charter as the state principleas well as phenomenon of terrorism which is always attached a term of “jihad” in Islamic tradition.Meanwhile, to conduct data and information, the research uses a qualitative approach as methodologyas well as documentation and interviews as a technique of collecting data. The collected data then isanalyzed and interpreted descriptively to get a proper conclusion. The result of the research shows thatthere are four variants in political elite in Muhammadiyah, i.e. transformative-idealistic, moderateidealistic,realistic-critical, and accommodative-pragmatic. The variations are deeply influenced by twofactors, i.e. sociological elite background and organizational.